2018
DOI: 10.4049/jimmunol.1701097
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor NFAT5 Promotes Migration and Invasion of Rheumatoid Synoviocytes via Coagulation Factor III and CCL2

Abstract: Fibroblast-like synoviocytes (FLSs) play a key role in the progression of rheumatoid arthritis (RA) as a primary component of invasive hypertrophied pannus. FLSs of RA patients (RA-FLSs) exhibit cancer-like features, including promigratory and proinvasive activities that largely contribute to joint cartilage and bone destruction. In this study, we hypothesized that the NF of activated T cell 5 (NFAT5), a transcription factor involving tumor invasiveness, would control the migration and invasion of RA-FLSs. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…In contrast, NFAT5-deficient macrophages exhibit reduced pro-inflammatory function, resulting in enhanced tumor growth in Lewis lung carcinoma and ID8 ovarian carcinoma models (43). Intriguingly, NFAT5-deficient macrophages show the reduced infiltration of effector CD8 + T cells into the tumor site (43), which is accordant with our findings of NFAT5 regulation of FLS migration (35). Together, in a sharp contrast to the tumorigenic role of NFAT5 in the cancer cells, NFAT5 in immune cells seems to escalate antitumor immunity by polarizing pro-inflammatory macrophages as well as promoting accumulation of CD8 + T cells adjacent to tumor masses.…”
Section: Role Of Nfat5 In the Pathogenesis Of Autoimmune And Inflammasupporting
confidence: 90%
See 3 more Smart Citations
“…In contrast, NFAT5-deficient macrophages exhibit reduced pro-inflammatory function, resulting in enhanced tumor growth in Lewis lung carcinoma and ID8 ovarian carcinoma models (43). Intriguingly, NFAT5-deficient macrophages show the reduced infiltration of effector CD8 + T cells into the tumor site (43), which is accordant with our findings of NFAT5 regulation of FLS migration (35). Together, in a sharp contrast to the tumorigenic role of NFAT5 in the cancer cells, NFAT5 in immune cells seems to escalate antitumor immunity by polarizing pro-inflammatory macrophages as well as promoting accumulation of CD8 + T cells adjacent to tumor masses.…”
Section: Role Of Nfat5 In the Pathogenesis Of Autoimmune And Inflammasupporting
confidence: 90%
“…Masuda et al first identified that NFAT5 mRNA is expressed in the RA synovia, particularly at sites of bone destruction (49). Along with this, our group has shown that NFAT5 is highly expressed in the RA-FLSs and that its expression in RA-FLSs is upregulated by the stimulation of pro-inflammatory cytokines such as IL-1β, TNF-α, and TGF-β (33, 35). Through the global gene expression profiling of RA-FLSs, we also found that NFAT5 is a major transcription factor for regulating the migration and invasion, an aggressive phenotype of RA-FLSs, which are mediated by the upregulation of CCL2- and tissue factor expressions as its downstream target genes (35).…”
Section: Role Of Nfat5 In the Pathogenesis Of Autoimmune And Inflammamentioning
confidence: 86%
See 2 more Smart Citations
“…Additionally, PLAUR, the receptor for PLAU, increased~3.3-fold. F3, coagulation factor III (alias tissue factor), increased~2.5fold; it participates in signal transduction outside of blood coagulation such as inflammation and cell migration [47]. Not all ECM-remodeling enzymes on the array were universally increased in response to poly (I:C) challenge of TNIP1deficient HaCaT keratinocytes.…”
Section: Tnip1 Deficiency During Poly (I:c) Exposure Promotesmentioning
confidence: 99%